DAMPAK PANDEMI COVID -19 TERHADAP KONDISI SOSIAL EKONOMI FOTOGRAFER ISTANO PAGARUYUNG - VICY ANDRIANY, M.Ec.Dev ANDRIANY (AL-ITTIFAQ: Jurnal Ekonomi Syariah, 2022)
The problem in this research is that there is a government policy to prevent the occurrence of crowds, including in tourist areas that have an impact on the livelihoods of community groups residing around tourist areas. In this case, one of the livelihoods affected is the photographer at Istano Basa Pagaruyung, Tanjung Emas District. The purpose of this study was to find out how the impact of the Covid-19 pandemic had on the socio-economic conditions of photographers at Istano Basa Pagaruyung, Tanjung Emas District.The type of research that the authors use is field research with a qualitative descriptive approach. Data collection techniques used in this study were interviews and documentation. The main informants in this study consisted of 10 photographers.The results of the study show that the Covid 19 pandemic has an impact on the socio-economic conditions of photographers at Istano Basa Pagaruyung. Where socially, it affects the level of tourist visits, communication among fellow photographers, economically it has an impact on income so that it is unable to meet daily needs.